A phase II, single‐arm, multicentre study of coltuximab ravtansine (SAR3419) and rituximab in patients with relapsed or refractory diffuse large B‐cell lymphoma. (24th March 2016) - Coiffier, Bertrand; Thieblemont, Catherine; de Guibert, Sophie; Dupuis, Jehan; Ribrag, Vincent; Bouabdallah, Réda; Morschhauser, Franck; Navarro, Robert; Le Gouill, Steven; Haioun, Corinne; Houot, Roch; Casasnovas, Olivier; et al.
Summary: In this phase II, multicentre, single‐arm study, 52 patients with relapsed/refractory diffuse large B‐cell lymphoma (DLBCL) received the anti‐CD19 antibody–drug conjugate coltuximab ravtansine (55 mg/m 2 ) and rituximab (375 mg/m 2 ) weekly for 4 weeks, then every 2 weeks for 8 weeks. The primary endpoint was objective response rate (ORR) by International Working Group Criteria. The primary objective was to reject the null hypothesis of an ORR of ≤40%. Among 45 evaluable patients, the ORR was 31·1% (80% confidence interval [CI]: 22·0–41·6%) and the primary objective was not met. The ORR appeared higher in patients with relapsed disease (58·3% [80% CI: 36·2–78·1%]) versus those refractory to their last (42·9% [80% CI: 17·0–72·1%]) or first‐line therapy (15·4% [80% CI: 6·9–28·4%]). Median progression‐free survival, overall survival and duration of response were 3·9 [80% CI: 3·22–3·98], 9·0 [80% CI: 6·47–13·67] and 8·6 (range: 0–18) months, respectively. The pharmacokinetics of both drugs were unaffected by co‐administration. Common adverse events included gastrointestinal disorders (52%) and asthenia (25%). No patients discontinued due to adverse events. In conclusion, coltuximab ravtansine with rituximab was well tolerated and yielded clinical responses in a subset of patients with relapsed/refractory DLBCL.